High-Efficiency Single-Cell Containment Microdevices Based on Fluid Control - Daiki Tanaka; Junichi Ishihara; Hiroki Takahashi; Masashi Kobayashi; Aya Miyazaki; Satsuki Kajiya; Risa Fujita; Naoki Maekawa; Yuriko Yamazaki; Akiko Takaya; Yuumi Nakamura; Masahiro Furuya; et al. (Micromachines, 2023)
In this study, we developed a comb-shaped microfluidic device that can efficiently trap and culture a single cell (bacterium). Conventional culture devices have difficulty in trapping a single bacterium and often use a centrifuge to push the bacterium into the channel. The device developed in this study can store bacteria in almost all growth channels using the flowing fluid. In addition, chemical replacement can be performed in a few seconds, making this device suitable for culture experiments with resistant bacteria. The storage efficiency of microbeads that mimic bacteria was significantly improved from 0.2% to 84%. We used simulations to investigate the pressure loss in the growth channel. The pressure in the growth channel of the conventional device was more than 1400 PaG, whereas that of the new device was less than 400 PaG. Our microfluidic device was easily fabricated by a soft microelectromechanical systems method. The device was highly versatile and can be applied to various bacteria, such as Salmonella enterica serovar Typhimurium and Staphylococcus aureus.